Kathy Martin writing up field notes in the lab trailer at La Pérouse Bay - Bazely, Dawn R. (1981)
Kathy Martin, doctoral student, Queen's University, writing up her daily field notes on the willow ptarmigan population of La Pérouse Bay, Manitoba, Canada.